Application of Problem Based Learning Model With Variation in The Condition of Learning Environment (Seating) to Increase Student Learning Activity and Critical Thinking Ability - Pelu, Musa (HISTORIKA, 2019)
The purpose of this research to improve learning activeness and critical thinking ability of college student in Learning History Courses in South Asia 1 by implementing  Problem Based Learning Model with variations of environmental conditioning (seating) at History Education Program FKIP UNS Year 2019.This research is a classroom action research (CAR). The research is conducted in two cycles which each cycle consists of planning, acting, observing, and reflecting. The subject of this research is college taking South Asia History Courses that consists of 42 college students. The data sources from lecturer, college students, learning process, and document. Data collection techniques are conducted by using observation, documentation, and interviews. Validity test technique uses triangulation which are triangulation of data or source and triangulation method. Data analysis uses interactive analysis. The research procedure uses a spiral model.The results show that: 1) the implementation of Problem Based Learning Model with variations of environmental conditioning (seating) can improve college student learning activeness. College students' learning activeness through pre- cycle observation is 28% or 12 college students, increase into 52% or  22 college students the cycle 1 and in the cycle II increases into 78% or 33 college students. This result has exceeded the set target which is minimum 75%. 2) the implementation of Problem Based Learning Model with variations of environmental conditioning (seating) can improve critical thinking ability of college student in Learning History Courses in South Asia 1 at History Education Program FKIP UNS Year 2019. Critical thinking ability of college student through pre-cycle observation is 61,4% or 26 college students, increases into 78,2 % or 33 college students in the cycle I and in the cycle II increases into 84,1% or 35 college students. This result has exceeded the set   target which is minimum 80%.Based on the results of research, it can be concluded by implementing Problem Based Learning Model with variations of environmental conditioning (seating) can improve learning activeness and critical thinking ability of college student in Learning History Courses in South Asia 1 at History Education Program FKIP UNS Year 2019.